Validation of the self-compassion scale in a sample of Italian special needs teacher - Ragni, Benedetta; Sulla, Francesco; Toto, Giusi Antonia; Limone, Pierpaolo (Frontiers in Psychology, 2023)
Special needs teachers may deal with highly stressful emotional situations in ways that compromise their ability to create and maintain quality learning environments and to provide support to the pupils under their care. Self-compassion (treating oneself with kindness, recognising one’s shared humanity, and being mindful when considering negative aspects of oneself) has been seen to function as a protective factor against teacher stress. Indeed, teachers’ stress resilience appeared to have been facilitated by self-compassion. The aim of the current study was to evaluate the factorial structure, reliability, and validity of the Self-compassion Scale (SCS) in a sample of Italian special needs teachers (R1). In addition, it was investigated whether the satisfactory internal reliability of the SCS is confirmed, with cut-off values of at least 0.70 for Cronbach's alpha (R2). Finally, the validity of the SCS criterion is assessed, assuming that each of its subscales will be related to anxiety, measured with the Generalized Anxiety Disorder scale 7 and with Resilience, measured with the Brief Resilience Scale (R3). A sample of 629 teachers was enrolled in this study and completed an online questionnaire. Overall, the confirmatory factor analysis showed good or acceptable indices of fit to the data supporting the use of SCS to measure self-compassion in Italian special needs teachers. The tool could be useful for future research to start exploring the self-compassion dimension at school, as a protective factor that may foster teachers’, and consequently, students’ wellbeing.